Group A Streptococcal Septic Hip Arthritis in a Child With Spastic Triplegic Cerebral Palsy. (August 2021) - Singh, Supriya; Davidson, Jacob; Carey, Timothy; Barton Forbes, Michelle; Cashin, Megan
Abstract : Reports of septic hip arthritis in children with cerebral palsy are exceedingly rare. This case report describes a 10-year-old boy with spastic triplegic cerebral palsy (Gross Motor Functional Classification System), who presented with fever and irritability. This case highlights the difficulties in diagnosing septic joint arthritis in patients with cerebral palsy who are nonverbal and have limited mobility. A high index of suspicion is necessary in this population when presented with fever and new limitations in mobility.